Predictors of in-hospital death in children with myocardial injury related to COVID-19 - César Augusto de Oliveira Souza Filho; Emilton Lima Junior (Journal of Infection in Developing Countries)
Introduction: Myocardial injury due to COVID-19 infection is associated with higher mortality rates, higher intensive care unit admissions, and greater levels of inflammatory and cardiac markers. However, given the smaller number of papers regarding pediatric patients, there is still scarce data about mortality predictors in this population. This study aims to identify independent predictors of in-hospital death among pediatric patients hospitalized with myocardial injury related to COVID‐19.